1984
DOI: 10.1037/0022-006x.52.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the K correction in the detection of psychopathology and its impact on profile height and configuration among young adult men.

Abstract: The standard Minnesota Multiphasic Personality Inventory with and without the K correction was compared for hit rate across patient (referral) and nonpatient (control) groups, both drawn from Air Force trainees. The impact of the K correction on profile height and configuration among the subjects in the referral group was also determined. Results show a total hit rate of 80.2% for the K correction and 78.3% for no K correction. Hit rate among the referral group only was 87.5% and 82.8% for K-corrected and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…K-corrected scores on the clinical scales were found to be no more effective than uncorrected scores in discriminating between normal and abnormal Air Force personnel (Wooten, 1984), adjusted and maladjusted college students (Heilbrun, 1963), and patients and nonpatients (Colby, 1989). However, both Wooten (1984) and Colby (1989) reported that K-corrected scores produced somewhat lower false negative rates (i.e., clinical cases identified as nonclinical), whereas uncorrected scores produced somewhat lower false positive rates (i.e., nonclinical cases identified as clinical). These classification-rate findings are consistent with the conclusions of Hsu (1986), who examined distributions of uncorrected and K-corrected scores of psychiatric patients, medical patients, and nonpatients.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…K-corrected scores on the clinical scales were found to be no more effective than uncorrected scores in discriminating between normal and abnormal Air Force personnel (Wooten, 1984), adjusted and maladjusted college students (Heilbrun, 1963), and patients and nonpatients (Colby, 1989). However, both Wooten (1984) and Colby (1989) reported that K-corrected scores produced somewhat lower false negative rates (i.e., clinical cases identified as nonclinical), whereas uncorrected scores produced somewhat lower false positive rates (i.e., nonclinical cases identified as clinical). These classification-rate findings are consistent with the conclusions of Hsu (1986), who examined distributions of uncorrected and K-corrected scores of psychiatric patients, medical patients, and nonpatients.…”
mentioning
confidence: 80%
“…However, both Wooten (1984) and Colby (1989) reported that K-corrected scores produced somewhat lower false negative rates (i.e., clinical cases identified as nonclinical), whereas uncorrected scores produced somewhat lower false positive rates (i.e., nonclinical cases identified as clinical). These classification-rate findings are consistent with the conclusions of Hsu (1986), who examined distributions of uncorrected and K-corrected scores of psychiatric patients, medical patients, and nonpatients.…”
mentioning
confidence: 95%
“…resolve the long-standing dispute about the MMPI K-correction, because although the criteria remain relatively constant, patient characteristics vary considerably (Wooten, 1984). The question about whether such score corrections can in general be expected to yield worthwhile gains cannot be definitively answered from the present research.…”
Section: Use Of the Cpi-emd Scale As A Standard Suppressor Variable Imentioning
confidence: 75%
“…resolve the long-standing dispute about the MMPI K-correction, because although the criteria remain relatively constant, patient characteristics vary considerably (Wooten, 1984).…”
Section: Use Of the Cpi-emd Scale As A Standard Suppressor Variable In Predictionmentioning
confidence: 99%
“…More research has been suggested to investigate its clinical utility in various populations (Dahlstrom, Welsh, & Dahlstrom, 1972;Greene, 1980). The K-correction has been found to reduce efficiency in the detection of psychopathology in some clinical populations by increasing the number of false positives (Bloom, 1977;Wooten, 1984). Whether the use of the K-correction enhances or reduces the accuracy of diagnosis and interpretation in clinical populations remains unresolved.…”
mentioning
confidence: 99%